THE STAGES OF FORMATION OF RUSSIAN SATIRICAL POETRY OF THE XVIII – XIX CENTURIES - Yulay Salavatovich Vakhitov (American Journals, 2024)
Russian satirical poetry highlights the main stages of formation and evolution of Russian satirical poetry over the course of two centuries, starting from the moment of its appearance in Russian literature in the first third of the XVIII century. The main genres of poetic satire that appeared during that period are given, as well as the key names of poets who had a significant impact on the development of this type of poetry.
Keywords: Satire, satirical, poetry, genre, poem, criticism.